Prevalence of Hypertension and Its Relationship with Stress Levels among Medical Students in Jakarta, Indonesia - Sanusi, Jesslyn Fresya; Ridjab, Denio A. (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Stress can occur in all groups, including late adolescents and university students. Repetitive and persistent exposure to stress can induce many other conditions, one of which is hypertension. Aging and the presence of risk factors could increase the prevalence of hypertension. This study aimed to determine the relationship between stress levels and the prevalence of hypertension in pre-clinical medical students.Method: This study used an analytical observational study design with a cross-sectional approach and simple random sampling of 212 pre-clinical medical students at the Atma Jaya Catholic University of Indonesia. The measuring instrument used was the K10 questionnaire, followed by blood pressure screening. The Kruskal-Wallis test using SPSS facilitated the univariate and bivariate data analysis.Results: The majority of the 212 respondents were female (61.8%), aged ranging from 18–21 years. Stress was identified in 49.1% of respondents, with mild stress (20.3%), moderate stress (15.6%), and severe stress (13.2%). Hypertension was detected in 11.8% of respondents, with 9.4% and 2.4% as grade 1 and 2 hypertension, respectively. High-normal blood pressure was detected in 20%. There was no significant relationship between stress levels and prevalence of hypertension among these pre-medical students (p-value for systolic pressure = 0.1318 and p-value for diastolic pressure = 0.8314). Conclusion: Although there is no relationship between stress levels and hypertension in medical students, however, concerns need to be emphasized regarding prevalence of hypertension stress. Further thorough evaluation and intervention are needed to prevent future complications in future medical doctors. Therefore, a healthy lifestyle is encouraged.